2019
DOI: 10.1371/journal.pone.0227080
|View full text |Cite
|
Sign up to set email alerts
|

High concentrations of middle ear antimicrobial peptides and proteins and proinflammatory cytokines are associated with detection of middle ear pathogens in children with recurrent acute otitis media

Abstract: Recurrent and chronic otitis media (OM) are often refractory to antibiotics due to bacterial persistence in biofilm within the middle ear. In vitro and in vivo studies have demonstrated that antimicrobial proteins and peptides (AMPs) are bactericidal against otopathogens, indicating potential therapeutic value for recalcitrant OM. We measured concentrations of 6 AMPs and 14 cytokines in middle ear effusion (MEE) from 67 children undergoing ventilation tube insertion for recurrent acute OM. Sixty one percent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
0
11
0
2
Order By: Relevance
“…Signalling regulation by host and pathogen factors within the middle ear during OM may lead to modification of timing and secretion of various cytokines, chemokines, interferons, and antimicrobial peptides from the mucosal epithelium or cells recruited to the site of activation. Importantly, the concentrations of antimicrobial peptides and proteins, and cytokines within MEF of children experiencing recurrent AOM are known to increase (Seppanen et al, 2019).…”
Section: Pathogen Recognition and Activation Of Signalling Pathways Within The Innate Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Signalling regulation by host and pathogen factors within the middle ear during OM may lead to modification of timing and secretion of various cytokines, chemokines, interferons, and antimicrobial peptides from the mucosal epithelium or cells recruited to the site of activation. Importantly, the concentrations of antimicrobial peptides and proteins, and cytokines within MEF of children experiencing recurrent AOM are known to increase (Seppanen et al, 2019).…”
Section: Pathogen Recognition and Activation Of Signalling Pathways Within The Innate Immune Responsementioning
confidence: 99%
“…Furthermore, in humans, lysozyme and ßdefensin 2 can synergistically partner to directly kill invading S. pneumoniae 6B (Lee et al, 2004) and protect against NTHi induced OM (Woo J. I. et al, 2014). Most recently, a study examining middle ear effusate from children experiencing recurrent AOM confirmed the importance of elevated antimicrobial protein (AP) and cytokines as potential markers for bacterial persistence and inflammation (Seppanen et al, 2019). Antimicrobial proteins or host defence peptides may offer future treatment options against polymicrobial infections (Bergenfelz and Hakansson, 2017;Batoni et al, 2021).…”
Section: Antimicrobial Factors Released By the Mucosal Epitheliummentioning
confidence: 99%
“…In these contexts, antimicrobial peptides (AMPs) are used as promising alternatives to counter bacterial infections and control microbial spreading. As antimicrobial resistance (AMR) is currently becoming a worldwide threat, the main focuses of research are: (i) to identify existing or new AMPs and to characterize their efficacy against prevalent microorganisms, including their mechanism of action and toxicity toward mammalian cells and/or blood cells; (ii) to assess the role of AMPs in modulating the pro-inflammatory cytokines and in adaptive immune mechanisms; and (iii) to identify new approaches for AMPs delivery [9].…”
Section: Introductionmentioning
confidence: 99%
“…The middle ear is encased in a bony cavity, despite rich vascular supply, it is hard to maintain sufficient concentration of antibiotics when given orally ( Barry et al, 1997 ). The concentration of β-lactam antibiotics transferred to the middle ear cavity is at about only 10–15% of the blood concentration ( Figueira et al, 2016 ; Seppanen et al, 2019 ). In addition, the tympanic membrane of AOM patients becomes thicker, which is a barrier for topical antimicrobial treatment.…”
Section: Introductionmentioning
confidence: 99%